2007
DOI: 10.1007/s11747-007-0017-5
|View full text |Cite
|
Sign up to set email alerts
|

Low price signal default: an empirical investigation of its consequences

Abstract: Low-price guarantees (LPG) signal the market position of a seller's offer price and promise to compensate consumers in case that information is erroneous. In this research, we demonstrate that when retailers default on the information provided by an LPG, consumer perceptions of the retailer suffer, but the extent of the damage depends on the conditions associated with the default. On the basis of attribution theory, we posit that consumers may attribute default to the retailer's opportunism but emphasize this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 34 publications
(59 reference statements)
1
25
0
2
Order By: Relevance
“…En el caso de Adidas, comparativamente, varios investigadores han encontrado diferencias y similitudes en la reacción emocional de los turistas ante los estímulos respecto al género (Collado et al, 2013;Gálvez et al, 2015;Gill et al, 2007). Al mismo tiempo, Ruiz et al (2014), al establecer comparaciones en sus resultados con otros estudios (Dutta et al, 2007), el género juega un papel moderador en la intención de compra. Entonces, sobre la base de estos sustentos, se establecen las siguientes hipótesis:…”
Section: El Efecto Moderador Del Género En La Intención De Compra De unclassified
See 1 more Smart Citation
“…En el caso de Adidas, comparativamente, varios investigadores han encontrado diferencias y similitudes en la reacción emocional de los turistas ante los estímulos respecto al género (Collado et al, 2013;Gálvez et al, 2015;Gill et al, 2007). Al mismo tiempo, Ruiz et al (2014), al establecer comparaciones en sus resultados con otros estudios (Dutta et al, 2007), el género juega un papel moderador en la intención de compra. Entonces, sobre la base de estos sustentos, se establecen las siguientes hipótesis:…”
Section: El Efecto Moderador Del Género En La Intención De Compra De unclassified
“…La elección de esta primera región para la realización del estudio empírico se fundamenta en la representatividad que esta zona tiene dentro del entorno vitivinícola. A este respecto, se observa que existen diferencias entre género en uno de los factores, lo que es coherente con el resultado de Kolyesnikova et al (2009), en la que encuentra una mayor orientación hacia los sentimientos en los enoturistas de un género que de otro y reafirma los trabajos que consideran la respuesta emocional a la compra es distinta entre géneros (Collado et al, 2013;Dutta et al, 2007;Galvez et al, 2015;Gill et al, 2007).…”
Section: Conclusiones E Implicacionesunclassified
“…A price guarantee may influence consumer behavior both before and after purchase (Dutta et al, 2007); the present study focuses on prepurchase effects. A PG also affects both the perceived value of the offer and visit intentions Dutta et al, 2006;Jain and Srivastava, 2000;Kukar-Kinney and Walters, 2003).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Dutta and Biswas (2005) found that consumers search more extensively after purchasing goods that carry low-price guarantee offers, while Dutta, Biswas, and Grewal (2007) found that defaulted PMGs reduce perceptions of value. Estelami, Grewal, and Roggeveen (2007) found that PMGs influenced post-purchase perceptions of perceived price and service quality even when retailers justifiably refused to honor the PMG.…”
Section: Introductionmentioning
confidence: 99%